Can Poverty Maps Direct Development Aid More Effectively to the Neediest? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Developing countries face many difficulties with targeting poverty alleviation programs towards people who need help the most. Often, detailed and accurate information is not readily available, and governments could end up in a double-bind -- distributing resources to individuals not in urgent need of assistance while excluding the poorest of the poor. Singapore Management University economics professor Tomoko Fujii was one of five international researchers who concluded that using ‘poverty maps’ combined with fine geographic targeting can deliver promising results.